Validity and Reliability of Methods to Determine Barbell Displacement in Heavy Back Squats: Implications for Velocity-Based Training. Issue 11 (November 2020) - Appleby, Brendyn B.; Banyard, Harry; Cormack, Stuart J.; Newton, Robert U.
Abstract : Abstract: Appleby, BB, Banyard, H, Cormack, SJ, and Newton, RU. Validity and reliability of methods to determine barbell displacement in heavy back squats: Implications for velocity-based training. J Strength Cond Res 34(11): 3118–3123, 2020—The purpose of this study was to investigate the validity and reliability of methods for determining barbell displacement during heavy back squats. Twelve well-trained rugby union players (mean ± SD 1 repetition maximum [1RM] 90° squat = 196.3 ± 29.2 kg) completed 2 sets of 2 repetitions at 70, 80, and 90% of 1RM squats. Barbell displacement was derived from 3 methods across 4 load categories (120–129, 140–149, 160–169, and 180–189 kg) including: a (a) linear position transducer (LPT) attached 65 cm left of barbell center, (b) 3D motion analysis tracking of markers attached to either end of a barbell, and (c) cervical marker (C7) (criterion measurement). Validity was calculated using the typical error of the estimate as a coefficient of variation (CV%) ±90% confidence interval (CI), mean bias as a percentage, and the Pearson product moment correlation ( r ). Intraday reliability was calculated using the intraclass correlation coefficient and the typical error expressed as a percentage of CV% ±90% (CI). Mean displacement for C7, LPT, and the barbell ends was 520, 529, and 550–564 mm, respectively. Validity of the LPT compared with the criterion was acceptable (CV% = 2.1–3.0; bias = 0.9–1.5%; r = 0.96–0.98), whereas that of the barbell ends was less (CV% = 2.7–7.5; bias = 4.9–11.2%; r = 0.71–0.97). The CV% reliability of the C7 marker across the load categories was 6.6%, the LPT 6.6%, and the barbell ends between 5.9 and 7.2%. Despite reliable measures, overestimation of displacement occurs as the tracking location moves to the barbell ends in weighted back squats. The LPT demonstrated high validity to the criterion and high trial-to-trial reliability.